Quality Of Life Questionnaire For Children With Cerebral Palsy (Cp Qol-Child): Translation And Cultural Adaptation To The Brazilian Portuguese Language - Braccialli, Lígia Maria Presumido [UNESP]; Braccialli, Ana Carla; Sankako, Andréia Naomi [UNESP]; Da Costa Dechandt, Maria Luiza [UNESP]; Da Silva Almeida, Vanessa [UNESP]; De Carvalho, Sebastião Marcos Ribeiro [UNESP] (Faculdade de Filosofia e Ciências, 2013)
The aim of this study was to verify the reliability of the Brazilian Portuguese version of the instrument Cerebral Palsy: quality of life questionnaire for children: primary caregiver questionnaire (CP QOLChild: primary caregiver) translated and culturally adapted. Thus, the translation and cultural adaptation of the instrument was made, and then the procedures to verify its reliability were performed. The translated and culturally adapted questionnaire was answered by 30 caregivers of children with cerebral palsy and inter- and intra-observer analysis followed. The data allowed the authors to identify an internal consistency rangering from 0.649 to 0.858, intra-observer reliability from 0.625 to 0.809 and inter-observer reliability from 0.498 to 0.903. The analysis suggests that the instrument has acceptable psychometry.
Keywords: Assessment instrument; Cerebral palsy; Quality of Life